Imputing genotypes in genome-wide association studies - Marchini, Jonathan (Henry Stewart Talks, 2008)
Tag SNPs and multi-marker predictors, The general problem of imputing genotypes for association studies, The IMPUTE method, Measuring accuracy of imputation, Results of using imputation in a real study, Using imputation for meta-analysis, The importance of strand alignment when using imputation
Archived at 2017/07/13